Hybrid Optical Wireless Network for Future SAGO-Integrated Communication Based on FSO/VLC Heterogeneous Interconnection - Zhitong Huang; Zhenfang Wang; Minglei Huang; Wei Li; Tong Lin; Peixuan He; Yuefeng Ji (IEEE Photonics Journal, 2017)
Free-space optics (FSO) and visible light communication (VLC) share the same optical wireless features, such as high data rate, license free, energy efficient, flexible access, and high degree of security. A hybrid optical wireless network based on FSO/VLC heterogeneous interconnection is presented here for future space-air-ground-ocean-integrated communication architecture, especially in the radio-frequency-sensitive (RF) or security-required environments. The functional modules of the hybrid network coordinator are defined, along with the implementation and deployment details. Three fundamental network-layer mechanisms are designed in the coordinator including user identification and localization, user mobility and handoff control, and routing and traffic management. An experimental platform is built to evaluate the transmission performance of the presented hybrid network, and a complete data aggregation/transmission/distribution procedure based on heterogeneous interconnection is first realized, which includes two-segment 1.0-m 450-Mb/s orthogonal-frequency-division-multiplexing-based VLC transmissions interconnected by one-segment 430-m 0.96-Gb/s on-off keying (OOK)-based nonturbulent FSO transmission, with the bit error rate under the forward-error-correction limit (3.8 × 10−3 ). The VLC transmission performances under three speed levels and FSO transmission performances under five typical air-quality conditions are experimentally demonstrated, which validate the feasibility of the proposed hybrid optical wireless network.